(untitled) (Revista Educação Especial em Debate, 2018)
Anna Maria Lunardi Padilha (Instituto de Pesquisa Heloísa Marinho) Andressa Mafezzoni Caetano (UFES) Denise Meyrelles de Jesus (UFES) Douglas Christian Ferrari de Melo (UFES) Edson Pantaleão Alves (UFES) Hiran Pinel (UFES) Ivone Martins de Oliveira (UFES) Jair Ronchi Filho (UFES) Lucyenne Matos da Costa Vieira Machado (UFES) Maria Almerinda de Souza Matos (UFAM) Marileide Gonçalves França (UFES) Reginaldo Célio Sobrinho (UFES) Rogério Drago (UFES) Rosana Givigi (UFS) Silvia Moreira Trugilho (EMESCAM) Sonia Lopes Victor (UFES) Vânia Maria Pereira dos Santos-Wagner Vitor Gomes (UFES)